Developing a New Approach to Temperature and pH Effects in the Modelling of the Adsorption Isotherms of Benzoic Acid onto Activated Carbon - Sohrab Ali Ghorbanian; Hossein Abolghasemi; Saeid Reza Radpour; Mohammad Ali Mousavian (Adsorption Science & Technology)
Two models for predicting the effects of temperature and pH on isotherm curves are presented in this paper. The development of these models was based on mathematical analysis and statistical tests; they are referred to as the temperature effect term (T.E.T.) and pH effect term (pH E.T.), respectively, below. The adsorption isotherms for benzoic acid (BA) onto granular activated carbon (GAC) have been measured at various temperatures (25–60°C) and pH values (2–8). The results obtained have been analyzed using the adsorption models of Langmuir, Freundlich, Redlich–Peterson, Toth, and Radke and Prausnitz. The Radke–Prausnitz (Ra–Pr) isotherm model gave the best fit to the experimental data. The T.E.T. and pH E.T. models predicted the isotherm curves with absolute relative errors of 1.19% and 2.19%, respectively. It was also demonstrated that these models gave successful predictions of isotherm curves at various temperatures and pH values. This was possible using a series of experimental data at specific temperatures and pH values. It was also shown that the models could be applied to the adsorption of any dilute organic acid onto any adsorbent which exhibited isotherm curves of a similar form to those obtained in the BA/GAC system.